Static and Dynamic Characteristic Simulation of Feed System Driven by Linear Motor in High Speed Computer Numerical Control Lathe - Yang Zeqing; Liu Libing; Wang Zuojie; Chen Yingshu; Xiao Quanyang (Institute of Advanced Engineering and Science, 2013)
In order to design the feed system of high speed Computer Numerical Control (CNC) lathe, the static and dynamic characteristics of feed system driven by linear motor in high speed CNC lathe were analyzed. The slide board was taking as the main moving part of the feed system, and the guide rail was the main support component of the linear motor feed system. The mechanical structure static stiffness of feed system is researched through the slide board statics analysis. The simulation results show that the maximum deformation of the slide board occurs in the middle of the slide board where the linear motor is placed. The linear motor feed system control model was established based on analysis of high-speed linear feed system control principle, and the linear motor feed system transfer function was established, and servo dynamic stiffness factors were analyzed. The control parameters of the servo system and actuating mechanism parameters of feed system on the effect of the linear motor servo dynamic stiffness were analyzed using MATLAB software. The simulation results show that the position loop proportional gain, speed loop proportional gain and speed loop integral response time are the biggest influence factors on servo dynamic stiffness. The displacement response is reduced under the cutting interference force step inputting, the servo dynamic stiffness is increased, the number of system oscillation is also reduced, and the system tends to be stable. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2813